(untitled) (Prilozi za orijentalnu filologiju, 2017)
Venetians, Germans and French, after travelling through Bosnia ad Herzegovina’s lands, spoke ironically about our cultural level under the Osmanlis’ rule, saying that Serb monks were peasant dullards, On the basis of their communication with the people and clergymen they stated the Serbs did not know the articles of religion, nor the formulae of Sunday prayers, sacraments of obedience; that the prists did not know themselves what they were telling the people; that only the minority knew the "Lord’s Prayer" and "faith"; that monks after the service went to work in the fields; that they did not speak any other languages, etc. The westem world did not see many a thing in the life of the Orthodox monasteries. For it, this remained a secret. In those foreign notes there was no mention of monks (biographers, icon-painters), printers, bookbinders, copyists, writers of introductions and postscripts to sacred writigs, skilfui envoys visiting Sultans, Russian Tsars and the Lords of Wallachia and Moldavia, the monks-merchants trading with Dubrovnik. Had the westem world seen that, then it would have learnt that it was not complete spiritual ignoranee and general negligence that dominated the Serb people and their church during the Osmanli-Turkish times. Sometimes even historians created that dark about understanding those times by accepting data uncritically.